PEMBUATAN La0,8Ca0,2MnO3 SEBAGAI KATODA PADA SOLID OXIDE FUEL CELL (SOFC) DAN KARAKTERISASINYA - Riska Ekawita (PERTETA, 2007)
ABSTRACT The making of La0,8Ca0,2MnO3 cathode material of solid oxide fuel cell from lanthanum oxide (La2O3), calcium oxide (CaO), and manganese carbonate hydrate (MnCO3.H2O) has been done using tape casting method. Time of firing the La0,8Ca0,2MnO3 varied. The values of t = 30 minutes, 60 minutes and 120 minutes. Microstructure of these materials was analyzed and characterized by means of their electric conductivity, XRD (x ray diffraction) and SEM (scanning electron microscope). It is found that formulated micro structure is orthorhombic. The result of measurement shows that density is in linear (positive) correlation with increasing of holding time of firing, porosity and coefficient of thermal expansion is negatively correlated with density and electric conductivity is in linear (positive) correlation with increase density. Diterima: 26 Pebruari 2007, Disetujui: 13 Mei 2007